KESENIAN KOBRO SISWO KOMUNITAS SINAR MUDA DESA SALAKAN KABUPATEN TEMANGGUNG (Kajian Holistik) - Kiki Fatmawati; Sutarno Haryono (Greget, 2018)
AbstrakPenulisan Skripsi ini bertujuan untuk mengungkap kesenian Kobro Siswo komunitas Sinar Muda dari segi kritik seni holistik untuk mendeskripsikan dan menganalisa tentang : (1) faktor genetik, membahas mengenai latar belakang terbentuknya kesenian Kobro Siswo komunitas Sinar Muda (2) faktor objektif, membahas komponen verbal dan komponen non-verbal, mendeskripsikan menjelaskan hubungan komponen non-verbal dan verbal (3) faktor afektif, menjelaskan respon atau tanggapan penghayat (4) menjelaskan makna kesenian Kobro Siswo komunitas Sinar Muda. Bentuk penelitian adalah penelitian kualitatif deskriptif, dengan menggunakan pendekatan kritik seni holistik. Teori yang digunakan untuk mengakaji kesenian Kobro Siswo komunitas Sinar Muda adalah : (1) Teori pragmatik untuk mengkaji komponen verbal dan koneksitas komponen verbal dan non-verbal, (2) Teori seni pertunjukan untuk mengkaji komponen non-verbal dan verbal. Simpulan didapat berdasarkan analisis koneksitas faktor genetik, objektif, afektif. Kesenian Kobro Siswo komunitas Sinar Muda merupakan kesenian yang berfungsi sebagai hiburan dan media dakwah. Kesenian Kobro Siswo komunitas Sinar Muda memberikan pesan moral yaitu mengajarkan pentingnya menjadi manusia yang memiliki semangat pantang menyerah dan selalu ingat kepada Tuhan Yang Maha Esa.Kata kunci: Kobro Siswo komunitas Sinar Muda, kritik seni holistik, pragmatik.AbstractThe aim of this thesis is to uncover the art of Kobro Siswo in the Sinar Muda community from a holistic art criticism perspective in order to describe and analyze: (1) the genetic factors, including a discussion of the background to the formation of the art of Kobro Siswo in the Sinar Muda community; (2) the objective factors, including a discussion of the verbal and non-verbal components and a description of the relationship between the verbal and non-verbal components; (3) the affective factors, including an explanation of the response or reaction of the audience; and (4) an explanation of the meaning of the art of Kobro Siswo in the Sinar Muda community. The form of the research is descriptive qualitative with a holistic art criticism approach. The theories used to study the art of Kobro Siswo in the Sinar Muda community are: (1) The theory of pragmatics to study the verbal component and the connection between the verbal and non-verbal components. (2) The theory of performing arts to study the verbal and non-verbal components. The conclusion is obtained based on an analysis of the connection between the genetic, objective, and affective factors, and shows that the art of Kobro Siswo in the Sinar Muda community is an art that functions both as entertainment and as a medium for religious proselytization. The art of Kobro Siswo in the Sinar Muda community present moral messages which teach about the importance of becoming a human being with a spirit that never gives up and always remembers Almighty God.Keywords: Kobro Siswo Sinar Muda community, holistic art criticism, pragmatic.